PERAN ORGANISASI SUBAK DALAM KOMUNIKASI ANTARA ORGANISASI DAN PEMERINTAH DALAM PEMANFAATAN AIR BAGI BIDANG PERTANIAN (STUDI PADA KABUPATEN BADUNG) - Ghoni, Khoirul Abror Ad-Dluha; Erlambang, Nanda; Haspiani, Nurhasanah; Ramadhina, Kaisyah Cika (FISIP UWP, 2025)
Abstract This research aims to understand the role of the Subak organization in communication between organizations and the government in the use of water for agriculture in Badung Regency, Bali. Based on the results of research conducted through in-depth interviews, observations, and Focus Group Discussions (FGD), it was found that there was a significant information gap between policies made by the government and their implementation in the field, thus hampering the effectiveness of these policies. Modernization and urbanization have also led to an increase in the conversion of agricultural land to non-agricultural uses, thereby reducing the irrigation function of Subak. In addition, the younger generation's participation in subak activities is decreasing because they are more interested in other sectors that are more modern and financially promising. Therefore, creative initiatives are needed to attract the attention of the younger generation and increase effective communication between Subak and the government. Keywords: Subak, Communication, Government, Modernization, Urbanization, Young Generation, Irrigation, Agriculture